A comparative study of the efficacy of WaveOne and NeoEndo retreatment file system for the removal of gutta percha from the root canal - Shweta V Sagare; Padma Chandra; Tawanpreet Kaur; Onkar Ganorkar; Abhijeet Khade; Sachin Dev Mehta (Wolters Kluwer Medknow Publications, 2021)
Background: Teeth with apical periodontitis that either persisted or developed after initial root canal treatment is most often indicated for retreatment procedure. The present study was conducted to compare the WaveOne and NeoEndo retreatment file system for the removal of gutta-percha from the root canal. Materials and Methods: Fifty extracted mandibular first premolars with single straight roots were divided into two groups, Group I-WaveOne and Group II-NeoEndo. All samples were scanned with cone-beam computed tomography after the root filling and retreatment procedures. The decrease in the volume of filling material after each retreatment protocol was measured. Results: The mean volume of gutta-percha in Group I before retreatment was 5.6 and in Group II was 5.3, after retreatment in Group I was 2.7, and in Group II was 4.2. The mean percentage reduction in Group I was 45.2% and in Group II was 23.8%. The difference was significant (P < 0.05). Conclusion: Both systems failed to completely remove gutta-percha. WaveOne was significantly more effective than the NeoEndo retreatment system.